Contribution of Industrial Sector’s In Corporate Social Responsibility (CSR) In India: Examining the Impact of Corporate Social Responsibility in India's Industrial Sector (Journal of Advances and Scholarly Researches in Allied Education, 2018)
As a developing country, India is at growing stage of its industries, agriculture, telecommunication and infrastructure. After adoption of LPG (Liberalization, privatization, globalization) during 1991, Indian economy opened to worldwide enterprises which to have pro’s and con’s as a threat to domestic industries but also brought immense of opportunity for growth of industries and other sector’s. This lead the Indian economy to bring up new idea of corporate social responsibility so as to p0revent concentration of economy as well as to balanced development of overall nation. By this research paper we are going to analyze the contribution pattern of industry and application section of CSR in India